Patients’ Perception of Nurses’ Performance Underlying Quality of Care - Latosa, Francis Rey; Del Rosario, Maria Shane (International Journal of Sustainability and Advanced Integrated Research, 2026)
Quality of care plays a crucial role in shaping patients’ experiences and satisfaction during hospitalization, with nurses serving as primary providers of direct patient care. Guided by Avedis Donabedian’s Quality-of-Care Model, which explains healthcare quality through the interaction of structure, process, and outcome, this study aimed to determine patients’ perceptions of the quality of care they receive in terms of timeliness, safety, communication, and overall satisfaction, and to examine the relationship between patients’ perception of quality care and nurses’ performance. A descriptive–correlational research design was employed. Data were gathered from hospitalized patients using a structured questionnaire designed to measure the different dimensions of nursing care. Descriptive statistics were used to analyze patients’ perceptions of care, while inferential statistics were utilized to determine the relationship between perceived quality of care and nurses’ performance. The results revealed that patients generally perceived the quality of nursing care positively across all four domains. Among the dimensions assessed, safety of care obtained the highest rating (WM = 3.56), followed by communication (WM = 3.55), overall satisfaction (WM = 3.53), and timeliness of care (WM = 3.45), all interpreted as Agree. These findings indicated that patients generally viewed nursing care as safe, responsive, and well communicated throughout their hospital stay. Patients reported that nurses responded to their needs, implemented safety procedures, and provided clear explanations regarding their care and treatment. The study concluded that nurses play a vital role in maintaining the quality of hospital care and improving patients’ satisfaction. Strengthening effective communication, ensuring adherence to patient safety practices, and maintaining timely nursing interventions remain essential in delivering quality patient-centered care. The findings highlighted the importance of continuous professional development, supportive work environments, and adequate staffing to further enhance nursing performance and sustain high standards of healthcare delivery.
Keywords: Quality of care; Performance; Perception